Daytime Sleepiness and Prosocial Behaviors in Kindergarten: The Mediating Role of Student-Teacher Relationships Quality - Longobardi, Claudio; Lin, Shanyan; Fabris, Matteo Angelo (Frontiers in Education, 2022)
High sleep quality is an important indicator of children's development as well as their good health. The aim of this study was to examine the relationship between excessive daytime sleepiness and prosocial behaviors in kindergarten-aged children, as well as exploring the possible mediating role of the teacher-student relationship underlying them. Participants included 60 teachers aged from 23 to 62 (M47.9, SD=9.73) in Italy who completed the student-teacher relationship scale, the daytime sleepiness questionnaire, and the strength and difficulties questionnaire. The children who were rated by teachers were 936 kindergarten children aged from 3 to 6 (M = 4.20, SD=0.91). The results showed that children’s daytime sleepiness significantly predicted all three dimensions of the student-teacher relationship. Specifically, children’s daytime sleepiness negatively predicted closeness and positively predicted conflict and dependence, and furthermore, these three dimensions of the relationship significantly predicted children’s prosocial behaviors. For older children in our sample, their daytime sleepiness was more significantly and positively associated with conflict in their relationship with teachers. Our data seem to support the importance of good teacher-student relationship quality in promoting a child’s positive social adjustment, especially in children with behavioral difficulties. Our data also suggest the importance of evaluating the quality of the student-teacher relationship as well as the sleep quality in the children’s daytime sleepiness.